Studio Arsitektur dan Relevansinya dalam Pedagogi Rancang Bangun - Suartika, Gusti Ayu Made; Swanendri, Ni Made; Saputra, Kadek Edi; Mudra, I Ketut (RUANG: Jurnal Lingkungan Binaan (SPACE: Journal of the Built Environment); Vol 10 No 1 (2023): April 2023, 2023)
This article raises a query in regard to the suitability of the 'studio' as a learning method in the field of architecture. Its existence is inspired by the central position of the studio in the curriculum for building design. The studio-based course absorbs a relatively more significant portion of resources, time, and energy compared to others which play a supporting or enriching role. This article applies an inductive approach and explorative method in both data collection and analysis. By considering the various components of influence in architectural learning – aspects of pedagogy, cultural diversification, social interests, and advances in science and technology –, the discussion and results of the study are described in three sub-topics. First is an exploration of a studio design-based education and its roles in learning. Second, it is a study of adapted learning methods that are initiated and implemented by various academic institutions in the same field. And third, it is an extraction of relevant learning methods for future education in the field of architecture.  Keywords: studio; learning methods; architecture; creativity; building design Abstrak Artikel ini membahas tentang kesesuaian ‘studio’ sebagai metode pembelajaran dalam pendidikan di bidang arsitektur. Keberadaannya diIlhami oleh sentralnya posisi studio di dalam kurikulum pembelajaran di bidang ilmu rancang bangun ini. Perkuliahan di studio menyerap porsi sumberdaya, waktu serta energi yang relatif jauh lebih besar, dibandingkan dengan berbagai mata kuliah lain yang berperan sebagai pendukung maupun pengkayaan. Artikel ini menerapkan pendekatan induktif dengan metode eksploratif baik dalam pengkoleksian data maupun analisisnya. Dengan mempertimbangkan berbagai komponen pengaruh terhadap pembelajaran di bidang arsitektur – aspek pedagogi, diversifkasi budaya, kepentingan sosial, dan kemajuan ilmu pengetahuan serta teknologi –, pembahasan serta hasil studi dijabarkan dalam tiga group sub-topik. Pertama, eksistensi studio dalam perannya sebagai wujud pembelajaran. Kedua, eksplorasi metode pembelajaran yang diimplementasikan oleh beragam institusi akademik di bidang yang sama. Dan ketiga, ekstraksi metode pembelajaran dalam ranah pendidikan di dunia arsitektur di masa yang akan datang. Kata kunci: studio; metode pembelajaran; arsitektur; kreativitas; rancang bangun